Population pharmacokinetic model of transdermal nicotine delivered from a matrix‐type patch. (6th September 2017) - Linakis, Matthew W.; Rower, Joseph E.; Roberts, Jessica K.; Miller, Eleanor I.; Wilkins, Diana G.; Sherwin, Catherine M. T.
Abstract : Aims: Nicotine addiction is an issue faced by millions of individuals worldwide. As a result, nicotine replacement therapies, such as transdermal nicotine patches, have become widely distributed and used. While the pharmacokinetics of transdermal nicotine have been extensively described using noncompartmental methods, there are few data available describing the between‐subject variability in transdermal nicotine pharmacokinetics. The aim of this investigation was to use population pharmacokinetic techniques to describe this variability, particularly as it pertains to the absorption of nicotine from the transdermal patch. Methods: A population pharmacokinetic parent‐metabolite model was developed using plasma concentrations from 25 participants treated with transdermal nicotine. Covariates tested in this model included: body weight, body mass index, body surface area (calculated using the Mosteller equation) and sex. Results: Nicotine pharmacokinetics were best described with a one‐compartment model with absorption based on a Weibull distribution and first‐order elimination and a single compartment for the major metabolite, cotinine. Body weight was a significant covariate on apparent volume of distribution of nicotine (exponential scaling factor 1.42). After the inclusion of body weight in the model, no other covariates were significant. Conclusions: This is the first population pharmacokinetic model to describe the absorption and disposition of transdermal nicotine and its metabolism to cotinine and the pharmacokinetic variability between individuals who were administered the patch.